Security Measure to Detect and Avoid Flooding Attacks using Multi-Agent System in MANETS - Bandana Mahapatra; Srikanta Patnaik (Institute of Advanced Engineering and Science, 2017)
Security is considered as one of the major challenge when it comes to infrastructure less and self dependent network without any centralized control. The vulnerability of Adhoc Network makes it susceptible to external attacks like flooding of hello messages or propagating fake routing messages etc. Such attacks generates a variety of problems like disturbing the network by flooding messages that results in waste of battery which is a vital resource to maintain the life span of the network. Most importantly cause agents to die when unable to reach destination due to fake routing messages causing a heavy loss on part of the nodes generating them to maintain the route knowledge. The paper proposes a novel technique to identify the flooding attack and measure to overcome them using Multi-Agent system.